2005
DOI: 10.1002/ffj.1511
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antimicrobial activities of the essential oil ofTriumfetta rhomboidea Jacq.

Abstract: The essential oil of the aerial parts of Triumfetta rhomboidea was analysed by GC and GC-MS and assayed for its antibacterial and antifungal activities. The main constituents identified were trans-β β β β β-caryophyllene (22.4%), kessane (14%) and caryophyllene oxide (13%). The antimicrobial tests showed a mild activity against Escherichia coli and Enterococcus hirae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The essential oil constituents reported [21] from the aerial parts of T. rhomboidea in terms of the major compound was similar to that found in this study with quantitative differences, while qualitatively relative amounts of the components which are somehow dissimilar from France growing plant. Correlation of the compounds from France growing plant with this study revealed that a high amount of β-caryophyllene and low amount of caryophyllene oxide were found in raw seeds oil of T. rhomboidea.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The essential oil constituents reported [21] from the aerial parts of T. rhomboidea in terms of the major compound was similar to that found in this study with quantitative differences, while qualitatively relative amounts of the components which are somehow dissimilar from France growing plant. Correlation of the compounds from France growing plant with this study revealed that a high amount of β-caryophyllene and low amount of caryophyllene oxide were found in raw seeds oil of T. rhomboidea.…”
Section: Resultssupporting
confidence: 85%
“…The plant is known as a weed, but a number of medicinal properties have been described for its different parts. In eastern Africa, T. rhomboidea is used in folk medicine for its abortive properties on the gravid mammalian uterus [21] and treatment of cancer among the tribal population in Kolli Hills, South India [22]. In traditional medicine, the bark and leaves of this plant are used for the treatment of diarrhea and dysentery [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal ulcers have been treated with the pounded roots of this species [3,16]. The flowers and fruits of T. rhomboidea have been used in gonorrhoea and leprosy treatment [9], while in East Africa powdered leaves of the plant are used in the treatment of anaemia [14,17]. Essential oils isolated from T. rhomboidea have been shown to possess antimicrobial activity [17], while its methanol extracts have also been shown to have antioxidant and antitumour activity in vivo [2,18].…”
Section: Triumfetta Rhomboideamentioning
confidence: 99%